Refractive Indices of Solids - Batsanov, Stepan S.; Ruchkin, Evgeny D.; Poroshina, Inga A. (SpringerBriefs in Applied Sciences and Technology, 2016)
This book highlights the basics of crystal optics methods and refractive index (RI) measurement techniques in various solids, as well as their scientific and technological applications. In addition to new techniques for cases when traditional techniques are impractical, such as for highly refracting powders, anomalous dispersion of light in the studied solid, or for colloids, it also describes conventional methods of RI measurement.